Transplanting highly active copper sites into stable MOFs for SAW humidity sensor with bio-inspired anti-pollution microhole array - Chengxu Lin; Jiaxin Liu; Xunyu Yuan; Shilong Peng; Shuang Xi; Hu Long; Zhiyong Liu; Guanglan Liao; Tielin Shi (Chemical Engineering Journal, 2026)

Physicochemical, microstructural, and Vis/NIR optical properties of kiwifruit during bruise-induced ripening - Youhua Bu; Shuai Li; Mingzhuang Lin; Chengxu Gong; Rui Wang; Wenchuan Guo (Postharvest Biology and Technology, 2026)

Isochrysis zhanjiangensis exhibits protective effects against metabolic abnormalities induced by high-fat diet in mice - Mei Wu; Yu Bai; Yanrong Li; Kang Chen; Jingyang Le; Jian Li; Chengxu Zhou; Spiros N. Agathos; Lin Zhang; Xiaojun Yan; Jichang Han (Marine Life Science & Technology, 2025)

Nutrient-mediated changes in growth, biochemical composition, and biosilica deposition in Cyclotella cryptica - Yuting Yu; Yan Sun; Yuhang Li; Zhengfeng Zhu; Lin Zhang; Jian Li; Spiros N. Agathos; Chengxu Zhou; Jichang Han (Journal of Oceanology and Limnology, 2025)

Development of a Mixotrophic Strategy for Efficient Cultivation of a Coccolithophore, Chrysotila roscoffensis - Luyao Zhang; Zhichao He; Yan Sun; Jian Li; Pengfei Cheng; Nicolas Spiros Agathos; Chengxu Zhou; Lin Zhang; Jichang Han (Journal of Ocean University of China, 2025)

Preparation of vanadium-titanium magnetite tailings/quartz sand monolithic composite and photocatalytic degradation of rhodamine B - Yawen Liu; Chengxu Liao; Lin Liu; Xiaping Zhu; Zhihui Chen; Dongxue Ren; Tianfeng Yang; Yonghua Sun (Minerals Engineering, 2024)

Effects of salinity and temperature on growth performance, biochemical composition, and biosilification process of Cyclotella cryptica - Yicun Zhao; Yan Sun; Zhengfeng Zhu; Yuhang Li; Lin Zhang; Jian Li; Spiros N. Agathos; Chengxu Zhou; Jichang Han (Algal Research, 2024)

An axenic strain reveals the responses of Phaeodactylum tricornutum to external organic carbon - Zhengfeng Zhu; Zhichao He; Jian Li; Chengxu Zhou; Yanrong Li; Lin Zhang; Xiaohui Li; Spiros N. Agathos; Jichang Han (Journal of Oceanology and Limnology, 2024)

Algae-bacteria consortia promotes the cell growth of marine microalgae Phaeodactylum tricornutum and Chrysotila roscoffensis - Jiaqi Fang; Yan Sun; Zhujun Zhu; Jian Li; Pengfei Cheng; Spiros N. Agathos; Yuanyuan Fu; Lin Zhang; Chengxu Zhou; Jichang Han (Algal Research, 2024)

Dynamic Doppler Characteristics of Maritime Airborne Corner Reflector - Lingang Wu; Shengliang Hu; Chengxu Feng; Yasong Luo; Zhong Liu; Li Lin (Journal of Marine Science and Engineering, 2024)
The maritime airborne corner reflector (ACR) is a radar reflector that can measure wind speed in an unknown sea area in real time over a long distance. To improve our understanding of how the ACR works, we investigated the Doppler characteristics of the ACR for the first time from a dynamic perspective. First, we constructed a radar echo signal model of the ACR. Then, we obtained the dynamic Doppler characteristics through pulse Doppler processing and discussed the special phenomenon of Doppler broadening. Finally, we proposed a rectangular window decomposition method to analyze the inner principle of the Doppler broadening phenomenon in more detail. In conclusion, this study provides valuable insights into the Doppler characterization of an ACR from a dynamic viewpoint, which contributes to enriching the basic theory of this equipment.

Regulatory dynamics of the higher-plant PSI–LHCI supercomplex during state transitions - Jianghao Wu; Shuaijiabin Chen; Chao Wang; Weijun Lin; Chao Huang; Chengxu Fan; Dexian Han; Dandan Lu; Xiumei Xu; SenFang Sui; Lixin Zhang (Molecular Plant, 2023)

Non-spherical collapse of a cavitation bubble induced by a rigid filament - Jinghan Pan; Chengxu Tu; Taohou Chen; Xufeng Xia; Pengfei Du; Fubing Bao; Jianzhong Lin (Ocean Engineering, 2023)

Morphological and physicochemical characteristics, biological functions, and biomedical applications of diatom frustule - Chenfei Yang; Chao Feng; Yuhang Li; Zheng Cao; Yan Sun; Xiaohui Li; Lin Zhang; Chengxu Zhou; Jichang Han (Algal Research, 2023)

Genome sequence of the novel freshwater Microcystis cyanophage Mwe-Yong1112-1 - Ruqian Cai; Dengfeng Li; Wei Lin; Weinan Qin; Lingting Pan; Fei Wang; Minhua Qian; Wencai Liu; Qin Zhou; Chengxu Zhou; Yigang Tong (Archives of Virology, 2022)

Zooplankton community size-structure change and mesh size selection under the thermal stress caused by a power plant in a semi-enclosed bay - Qianwen Shao; Yifeng Zhu; Meixia Dai; Xia Lin; Chengxu Zhou; Xiaojun Yan (Acta Oceanologica Sinica, 2020)